Agreement between trainees and supervisors on first-year entrustable professional activities for anaesthesia training. (July 2020) - Marty, Adrian P.; Schmelzer, Sarah; Thomasin, Reto A.; Braun, Julia; Zalunardo, Marco P.; Spahn, Donat R.; Breckwoldt, Jan
Abstract: Background: Entrustable professional activities (EPAs) are commonly developed by senior clinicians and education experts. However, if postgraduate training is conceptualised as an educational alliance, the perspective of trainees should be included. This raises the question as to whether the views of trainees and supervisors on entrustability of specific EPAs differ, which we aimed to explore. Methods: A working group, including all stakeholders, selected and drafted 16 EPAs with the potential for unsupervised practice within the first year of training. For each EPA, first-year trainees, advanced trainees, and supervisors decided whether it should be possible to attain trust for unsupervised practice by the end of the first year of anaesthesiology training (i.e. whether the respective EPA qualified as a 'first-year EPA'). Results: We surveyed 23 first-year trainees, 47 advanced trainees, and 51 supervisors (overall response rate: 68%). All groups fully agreed upon seven EPAs as 'first-year EPAs' and on four EPAs that should not be entrusted within the first year. For all five remaining EPAs, a significantly higher proportion of first-year trainees thought these should be entrusted as first-year EPAs compared with advanced trainees and supervisors. We found no differences between advanced trainees and supervisors. Conclusions: The views of first-year trainees, advanced trainees, and supervisors showed high agreement. Differing views of young trainees disappeared after the first year. This finding provides a fruitful basis to involve trainees in negotiations of autonomy.